2019
DOI: 10.1177/1540415319856326
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Patients’ Perception About Behaviors of Humanized Nursing Care

Abstract: Introduction: One of the greatest challenges that health professionals face is providing humanized care, especially when technological advancements contribute to the depersonalization of care delivery. In this sense, nursing care not only requires the nurse to be scientific, academic, and clinical but also a humanitarian and moral agent, as a partner in human transactions. Method: Quantitative, descriptive, and transversal study. In a nonprobabilistic sampling for convenience, in 150 surgical patients, with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…( 16 ) Meanwhile, Mexico recently reported that 67% of the participants from the context of surgical hospitalization, perceived the behavior of humanized care as favorable. ( 17 ) Nevertheless, another Colombian experience reported that only a little more than half of the patients studied (54.5%) considered that they “always” perceive the humanized-care behavior. ( 18 )…”
Section: Discussionmentioning
confidence: 97%
“…( 16 ) Meanwhile, Mexico recently reported that 67% of the participants from the context of surgical hospitalization, perceived the behavior of humanized care as favorable. ( 17 ) Nevertheless, another Colombian experience reported that only a little more than half of the patients studied (54.5%) considered that they “always” perceive the humanized-care behavior. ( 18 )…”
Section: Discussionmentioning
confidence: 97%
“…15 Long 16 found that continuous nursing can help with improving children's mood, communicating the treatment plan to children's families, and improving children's immune function and living conditions through diet and proper exercise, which is consistent with previous research results. 17,18 Continuous nursing can serve to meet the needs of patients, improve the overall level of nursing, improve patient satisfaction, promote more effective nursing work, and promote improvement of the doctor-patient relationship. Kirolos et al 19 found that continuous nursing can improve nursing satisfaction among children with pneumonia as well as avoid medical disputes.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo que avaliou a percepção dos pacientes cirúrgicos sobre a assistência de enfermagem humanizada corrobora a necessidade de repensar a assistência sob a lógica da integralidade e da humanização, o que permitiu identificar que as percepções dos pacientes alcançaram pontuações favoráveis quando a equipe de enfermagem fornecia cuidados pautados na humanização 19 . Comportamentos relacionados ao respeito, a dignidade e a privacidade sem distinção de crenças e valores, reconhecimento das necessidades individuais, valorização dos sentimentos, comunicação efetiva e atitudes que transmite tranquilidade e segurança durante a hospitalização foram determinantes 19 .…”
Section: Cuidado Oferecido Pelos Profissionais De Enfermagem Durante unclassified